Feeling My Way From the University Into the Wilderness and Back Again - Kull, Robert (Journal of the Canadian Association for Curriculum Studies, 2016)
This narrative essay unfolds in two parts. Part 1—Feeling My Way into Embodied Research—reflects on my doctoral fieldwork, which involved living for a year in complete solitude in the remote wilderness of southern Chile. The life events that shaped this experience, including childhood, education, early career, and graduate studies, laid the physical, emotional, intellectual and spiritual groundwork for the project. A key challenge was to develop a methodology appropriate to the unusual context of my study. My methodology was grounded in mindful observation layered with analytic introspection, loosely based on autoethnography. Part 2 Feeling My Way into Embodied Writing—recounts the process of transforming my 900 page wilderness journal into a doctoral dissertation that was both academically rigorous and accessible to audiences. I abandoned the traditional academic approach of using a conceptual framework to organize the work in favour of a first person narrative, punctuated with analytic essays. Rather than write a dissertation about solitude, I let the voices of solitude speak directly to readers and evoke for them the actual experience as I had lived it.